Investigating influential factors of technology adoption in construction safety management - Lee, Karen Pei Han (2021)
Fatal and near-fatal accidents continue to plague the construction industry. The exacerbation of construction safety is attributed primarily to poor safety awareness and lack of innovativeness. The point is, advancements in safety technologies can ameliorate construction safety, thus it is odd that the construction industry is slow to adopt new technologies. As such, this calls for empirical evidence to acquire a deeper insight into this phenomenon. The present study bridges the gap in knowledge and practice by evaluating the potentials of safety technology, factors influencing its adoption and strategies to raise the adoption level. Following a detailed literature review, a questionnaire survey was developed encompassing 10 potentials, 20 factors and 10 strategies that were identified. A total of 133 responses were gathered from the Malaysian construction practitioners. The survey data was subjected to descriptive statistics and exploratory factor analysis. Findings revealed that the leading potentials of safety technologies are: improve hazard identification, reinforce safety planning, and enhance safety inspection. All the considered factors were perceived to be significant, with the most influential factors being expertise and skill of project team, proven technology effectiveness, top management support, government promotion and initiative, and technology reliability. As for the potential strategies, it is uncovered that reinforcement of training and education is more likely to raise the safety technology adoption, followed by provision of government incentives and establishment of government mandates. Four underlying factors were found from factor analysis, namely organisation’s commitment and technology orientation, supporting technological attributes, personal perception and performance expectancy, and government support. A possible limitation of this research is its focus on a small group of construction practitioners, thus limiting the generalisability of the findings. This study provides more profound insights into the factors influencing safety technology adoption and recommends strategies to promote the adoption. These findings could potentially assist the practitioners in making informed decisions on implementing safety technologies, which will ultimately lead to enhanced safety performance. This study also supplements the existing body of knowledge around this under-explored area in the construction management studies.